Pengaruh Brand Awarness, Brand Image, dan Brand Trust terhadap Brand Loyalty pada Pelanggan Produk Kosmetik Make Over di Kota Surabaya - Rohma Kusuma Zulianti; Jojok Dwiridotjahjono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine and assess the influence of brand awareness, brand image and brand trust on brand loyalty among cosmetics buyers in Surabaya. This research focuses on people who buy cosmetic goods in Surabaya. The sample size was 100 participants, taken using purposive and cluster sampling procedures. This research data was analyzed using the